Pengaruh Motivasi Kerja dan Etika Bisnis Islam Terhadap Kualitas Pelayanan Karyawan pada Bank Syariah Mandiri Muara Bulian - Nurhikmah Nurhikmah; Zulqarnain Zulqarnain; Pikri Pikri; Mayasari Mayasari (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The influence of work motivation and Islamic business ethics on the quality of employee service at Bank Syariah Mandiri Muara Bulian, Journal, Islamic Economics/Banking and Sharia Financial Institutions, The establishment of services based on relationships with customer satisfaction is the key to retaining customers and includes providing benefits financial and social as well as structural ties with customers. A service must decide how much relationship-based service it should perform to each market segment and customer, from casual, relative, responsible, proactive to full partnership. Administrative information contains so many meanings, has various functions, raises so many expectations. The method used in this study is a survey method, which was carried out at Bank Syariah Mandiri Muara Bulian using a probability sampling technique with a total sample of 52 employees. The hypothesis in the study 1) there is an influence between work motivation on the quality of employee service of 0.7553. 2) there is an influence between Islamic business ethics on employee service quality of 0.535. 3) there is an influence between work motivation and Islamic business ethics on the quality of employee service of 0.945. Hypothesis testing uses path analysis with a significant level of a = 0.05. Based on the findings of this study, the better the work motivation and Islamic business ethics, the better the quality of employee service.